(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In a 2008 publication, a systematic linguistic and semantic reappraisal of the text of Botorrita 1, based on all previous interpretation proposals, has uncovered the eight-part structure of the law about the maintenance of the triangular grove of the Sacred Oaks: § I. Title (l. 1-A); § II. Opening clause (l. 1-A); § III. Main decree together with its exceptions and the penalty for whom contravenes (l. 1/4-A); § IV. Particular provisions for keeping the territory clean (l. 4/7-A); § V. Provision about the harvest (l. 7/9- A); § VI. Particular provisions for the irrigation (l. 9/10-A); § VII. Final clause (l. 10/11-A); § VIII. The signataries (l.11-A y cara B). The present contribution illustrates all levels of the grammatical system underlying the inscription, which do not require special explanations but fit into what we know of the development of Common Celtic as well as of other Celtiberian or Celtic texts.